1998
DOI: 10.3109/10641969809053223
|View full text |Cite
|
Sign up to set email alerts
|

Significant Role of the Increase in Renin-Angiotensin System in Cardiac Hypertrophy and Renal Glomerular Sclerosis in Double Transgenic Tsukuba Hypertensive Mice Carrying Both Human Renin and Angiotensinogen Genes

Abstract: Tsukuba hypertensive mice (THM) are a hypertensive model prepared by mating a transgenic mice with human renin gene and a transgenic mice with human angiotensinogen gene. In the present study, we examined effects of renin-angiotensin system (RAS) on cardiac hypertrophy and renal disorders using Tsukuba hypertensive mice. While THM showed an increase of about 30 mmHg in systolic pressure compared to C57BL/6 mice employed as normal control animals, the increase in blood pressure was not observed in the mice to w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 18 publications
0
18
0
1
Order By: Relevance
“…Furthermore, it has been reported that the inhibitory effect on the activity of ACE in the heart and kidney persists for a longer period than that in blood after administration of ACEI (45). Since ACEIs prevent left ventricular hypertrophy even at doses at which blood pressure does not fall (46,47), the suppression of tissue RAS is believed to be important for cardiac hypertrophic suppression, and reports supporting Kai et …”
Section: Discussionmentioning
confidence: 51%
“…Furthermore, it has been reported that the inhibitory effect on the activity of ACE in the heart and kidney persists for a longer period than that in blood after administration of ACEI (45). Since ACEIs prevent left ventricular hypertrophy even at doses at which blood pressure does not fall (46,47), the suppression of tissue RAS is believed to be important for cardiac hypertrophic suppression, and reports supporting Kai et …”
Section: Discussionmentioning
confidence: 51%
“…Conversely, transgenic mice carrying both human AOGEN and renin genes incur glomerulosclerosis and phenotypic alterations in mesangial cells. 17,18 Biochemical and pharmacological studies have revealed that AT 1 undergoes rapid internalization on agonist stimula-tion and then recycles back to the plasma membrane. 19 -22 Although the recycling of receptors to the plasma membrane is a notable event, the molecular mechanisms of this process are not well understood.…”
mentioning
confidence: 99%
“…Conversely, transgenic mice carrying both human AOGEN and renin genes incur glomerulosclerosis and phenotypic alterations in mesangial cells. 17,18 Biochemical and pharmacological studies have revealed that AT 1 undergoes rapid internalization on agonist stimula- …”
mentioning
confidence: 99%
“…In THM, the occurrence of severe cardiac hypertrophy and glomerulosclerosis, in comparison with the degree of hypertension, has been reported. 3 L -158,809 [5,7-dimethyl-2-ethyl-3-[{2'-(1H-tetrazol-5-yl)is a selective AII receptor antagonist with high potency, good per os absorption, long duration and antihypertensive efficacy after a single dose equal to that of angiotensin converting enzyme inhibition, and does not have AII agonist activity. 4,5 The affinity of L-158,809 for the AII type 1 receptor (AT1R) and its potency for the inhibition of AII responses in a variety of tissues and in vitro preparations is subnanomolar (IC50=0.2-0.8 nmol/L).…”
mentioning
confidence: 99%
“…In THM, the occurrence of severe cardiac hypertrophy and glomerulosclerosis, in comparison with the degree of hypertension, has been reported. 3 L -158,809 [5,7-dimethyl-2-ethyl-3-[{2'-(1H-tetrazol-5-yl)…”
mentioning
confidence: 99%